Hepatoprotective Effects of Herbal Medicines against Non-alcoholic Fatty Liver Disease: A Systematic Review of Clinical and In Vivo Studies - Moayyedkazemi, Alireza; Amraei, Morteza; Nejad, Efran B.; Moghaddam, Ali; Karami, Kimia; Baharvand, Parastoo (Current Traditional Medicine, 2021)
Background: In this systematic review, we mainly emphasis on the current advances on the hepatoprotective effects of medicinal herbs in the Non-alcoholic Fatty Liver Diseases (NAFLD) treatment. Methods: This review was done based on the 06- PRISMA guideline and registered in the CAMARADES- NC3Rs Preclinical Systematic Review and Meta-Analysis Facility (SyRF) database. We did all the research in scientific databases in some English language databases, such as Web of Science, PubMed, Scopus, Google Scholar, and EMBASE, with no limitation in time to find the in vivo and clinical investigations on hepatoprotective effects of herbal medicines on non-alcoholic fatty liver disease. The selected words and terms for our search were: “fatty liver”, “extract”, “essential oil”, “clinical trial”, “herbal medicine”, “medicinal plants”, and “non-alcoholic fatty liver”. Results: Out of 21230 papers, 28 papers including 21 in vivo (75.0%), and 7 clinical trials (25.0%) up to 2020, met the inclusion criteria for discussion in this systematic review. The most part used of plants were leaves (14, 50.0%), rhizome (4, 14.3%), seeds (3, 10.3%), respectively. The most formulations of medicinal herbs were extracts essential oil (9, 35.7%) followed by ethanolic extract (5, 17.8%). The most animals used in vivo studies were rats (12, 42.8%) followed by mice (9, 32.1%). The obtained results also showed that the most period of administrated by these plants were 12 weeks (6, 21.4%), 2 months (6, 21.4%), and 30 days (3, 10.7%), respectively. Conclusion: The obtained findings of the present review demonstrated that medicinal plants due to high availability, high efficacy, and low or minimal toxicity are considered as a valuable and proper alternative to chemical synthetic drugs to treat and prevent of NAFLD. However, further studies especially on the toxicity of these agents are required to approve these recommendations.
Keywords: natural product